Elimination of inhaled 3,3′-dichlorobiphenyl (CB11) and the formation of the 4-hydroxylated metabolite - Hu, Xin (2013)
The recent discovery of 3,3′-dichlorobiphenyl (CB11) as a byproduct of pigment manufacturing underscores the urgency to investigate its biological fate. The high level and ubiquity of atmospheric CB11 indicates that inhalation is the major route of exposure. However, few data on its uptake and elimination exist. A time course study was performed exposing male Sprague-Dawley rats to CB11 via nose-only inhalation with necropsy at 0, 4 and 8 h post exposure. An analytical method for CB11 and mono-hydroxylated metabolites employing pressurized liquid extraction and gas chromatography-mass spectrometry yielded efficient recovery of CB11 (73±9%) and its metabolite 3,3′-dichlorobiphenyl-4-ol (4-OH-CB11) (82±12%). Each rat was exposed to 106 μg/m(3) vapor-phase CB11 for 2 h and received an estimated dose of 1.8 μg. Rapid apparent first-order elimination of CB11 was found in lung, serum and liver with half-lives of 1.9, 1.8 and 2.1 h, respectively. 4-OH-CB11 was detected in the liver but not the lung or serum of exposed animals and displayed apparent first-order elimination with a 2.4 h half-life. This study demonstrates rapid metabolism of CB11 and elimination of 4-OH-CB11 and suggests that the metabolite is not retained in the body but is susceptible to further biotransformation.